Biopolitics, discipline, and hydro‐citizenship: Drought management and water governance in England. Issue 2 (19th February 2019) - Sarmiento, Eric; Landström, Catharina; Whatmore, Sarah
Abstract : In this paper we argue that English drought management rests on two imaginaries of hydrocitizenship: an economic/instrumental imaginary that frames people primarily as "customers, " and an imaginary that focuses more on the affectively charged, personal engagements between individuals and "hydrosocial" spaces. These imaginaries, we contend, roughly correspond with the two modalities of a form of governance referred to by Michel Foucault as biopower: biopolitics and discipline. Drawing on fieldwork conducted as part of a large interdisciplinary research project on drought in the UK, we sketch the contours of English drought management, exploring in particular the "macro‐scale" elements of drought management (the biopolitical modality), premised on computer simulation modelling, and the elements of drought management that focus on the level of individual people (the disciplinary modality), premised in part on the work of local environmental organisations. The difference between the two notions of hydrocitizenship informing these two modalities of management, we conclude, produces tensions that potentially undermine water governance as it is currently organised in the UK. Ultimately, our goal in the paper is not solely to expose or critique existing governance efforts or the power relations therein, but rather to examine the interplay of governmentalities that constitute drought management in order to illuminate and expand the potential for "being governed differently." Abstract : In this paper we argue that English drought management rests on two imaginaries of hydrocitizenship, which correspond with the two modalities of a form of governance referred to by Michel Foucault as biopower: biopolitics and discipline. Drawing on fieldwork conducted as part of a large interdisciplinary research project on drought in the UK, we explore the "macro‐scale" elements of drought management (the biopolitical modality), premised on computer simulation modelling, and the elements of drought management that focus on the level of individual people (the disciplinary modality), premised in part on the work of local environmental organisations. The difference between the two notions of hydrocitizenship informing these two modalities of management, we conclude, produces tensions that potentially undermine water governance as it is currently organised in the UK.